Max Weber: entre a Sociologia e a Psicologia - Secches, Pedro (2020)
At the end of the 19th century, the role of Psychology in the analysis of the social reality of the individual, despite all its advance in the experimental field, was something deeply questioned by the nascent sociological community. Max Weber's apparent rejection of a possible psychological contribution to the understanding of the complex relationship between man and society, at first, seems consistent with the context of his time and his environment. However, thorough the reading of Weber's work, especially his methodological texts, it becomes clear that this perception does not hold true, given that, despite his critical tone, Weber, in fact, incorporated psychological elements into his ideal-typical analysis. Although not widely studied, the influence of psychology on Weber's sociology, as well as his position on the relationship between both sciences, is imperative to understand the importance of the German sociologist's thought and methodology in the establishment of a psychosocial science. It is possible to say, therefore, that Weber was one of the pioneers to break the barrier imposed between Sociology and Psychology by the late 19th and early 20th centuries. In order to deepen the study of this aspect of Weberian Sociology, this thesis explore the way in which the sciences of Sociology and Psychology developed, seeking in their historical and philosophical origins, the root for the creation of a barrier between the two sciences and to the development of psychosocial knowledge. Additionally, the objective of this thesis is to explore, through reading Weber's texts, the reason for Weber's criticism of the scientific practice of Psychology and the psychologists of his time. With this, it is intended to establish the real relationship of Weberian thought with Psychology, in addition to indicating a possible relationship of complementarity between Weberian Comprehensive Sociology and the psychoanalytic theory of another important thinker that broke through the barrier that separated the study of society versus study of the individual: Sigmund Freud